PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS E BOOK PADA MATERI RENANG SISWA SMP - Rizki Gani; Aref Vai; Muhammad Imam Rahmatullah (Pendekar : Jurnal Pendidikan Berkarakter, 2025)
This research aims to develop and validate an interactive e-book as instructional material for swimming for junior high school students. The background of this study is the limited conventional teaching materials that often make students less motivated in understanding abstract and complex concepts. The e-book was developed using the Richey & Klein model, which consists of three main stages: analysis, design, and development. The research subjects included three expert validators (material, media, and language) and 30 students for a limited trial. Data was collected through interviews, observations, and validation sheets, then analyzed descriptively. The validation results show that the e-book reached a "Very Valid" category with an overall percentage of 88.4%. Specifically, the material aspect received 90%, the media aspect 86.67%, and the language aspect 88.6%. The limited trial results also indicated that the product is "Very Practical" with an average score of 3.62, showing a positive student response. Therefore, this study concludes that the interactive swimming e-book is highly valid and suitable for use as a learning medium to enhance students' understanding and learning motivation.